Total arterial compliance estimated by a novel method and all-cause mortality in the elderly: the PROTEGER study - Papaioannou, Theodore G. (Springer Netherlands, 2014)
Aortic stiffness, assessed by carotid-to-femoral pulse wave velocity (PWV), often fails to predict cardiovascular (CV) risk and mortality in the very elderly. This may be due to the non-linear association between PWV and compliance or to blood pressure decrease in the frailest subjects. Total arterial compliance (C(T)) is the most relevant arterial property regarding CV function, compared to local or regional arterial stiffness. A new method for C(T) estimation, based on PWV, was recently proposed. We aimed to investigate the value of C(T) to predict all-cause mortality at the elderly. PWV was estimated in 279 elderly subjects (85.5 ± 7.0 years) who were followed up for a mean period of 12.8 ± 6.3 months. C(T) was estimated by the formula C(T) = k × PWV(−2); coefficient k is body-size dependent based on previous in silico simulations. Herein, k was adjusted for body mass index (BMI) with a 10 % change in BMI corresponding to almost 11 % change in k. For a reference BMI = 26.2 kg/m(2), k = 37. Survivors (n = 185) and non-survivors (n = 94) had similar PWV (14.2 ± 3.6 versus 14.9 ± 3.8 m/s, respectively; p = 0.139). In contrast, non-survivors had significantly lower C(T) than survivors (0.198 ± 0.128 versus 0.221 ± 0.1 mL/mmHg; p = 0.018). C(T) was a significant predictor of mortality (p = 0.022, odds ratio = 0.326), while PWV was not (p = 0.202), even after adjustment for gender, mean pressure and heart rate. Age was an independent determinant of C(T) (p = 0.016), but not of PWV. C(T), estimated by a novel method, can predict all-cause mortality in the elderly. C(T) may be more sensitive arterial biomarker than PWV regarding CV risk assessment.